Reconciling the role of organic matter pathways in aquatic food webs by measuring multiple tracers in individuals. Issue 12 (1st December 2015) - Jardine, Timothy D.; Woods, Ryan; Marshall, Jonathan; Fawcett, James; Lobegeiger, Jaye; Valdez, Dominic; Kainz, Martin J.
Abstract : Few studies measure multiple ecological tracers in individual organisms, thus limiting our ability to differentiate among organic matter source pathways and understand consequences of dietary variation and the use of external subsidies in complex food webs. We combined two tracers, stable isotope (SI) ratios and fatty acids (FA), to investigate linkages among ecological compartments (water column, benthos, riparian zone) in food webs in waterholes of a dryland river network, the Border Rivers in southwestern Queensland, Australia. Comprehensive analyses of sources (plankton, periphyton, leaf litter, riparian grasses) and animals (benthic insects, mollusks, large crustaceans, fishes) for SI and FA showed that all three zones contribute to animal biomass, depending on species and life stage. Large fishes derived a subsidy from the riparian/floodplain zone, likely through the consumption of terrestrial and semi‐aquatic insects and prawns that fed on detritivorous insects. Importantly, post‐larval bony bream ( Nematalosa erebi ) and golden perch ( Macquaria ambigua ) were tightly connected to the water column, as evidenced by 13 C‐depleted, 15 N‐enriched isotope ratios and a high content of plankton‐derived polyunsaturated fatty acids (eicosapentaenoic acid [EPA; 20:5ω3] and docosahexaenoic acid [DHA; 22:6ω3]). These observations were consistent with expectations from nutritional requirements of fish early life stages and habitat changes associated with maturity. These results highlight the importance of high‐quality foods during early development of fishes, and show that attempting to attribute food‐web production to a single source pathway overlooks important but often subtle subsidies that maintain viable populations. A complete understanding of food‐web dynamics must consider both quantity and quality of different available organic matter sources. This understanding can be achieved with a combined SI and FA approach, but more controlled dietary studies are needed to estimate how FA profiles are modified by animals when consuming a diverse range of diets of variable quality.